A Civil Law Perspective on the Music Copyright Dispute: Agnez Mo vs. Ari Bias - Ayni Suwarni; Ema Farida (Faculty of Law, Universitas Pekalongan, 2025)
Copyright disputes in the music industry often arise due to unclear mechanisms for royalty payments. The case of Ari Bias vs. Agnez Mo, regarding the unauthorized use of the song